Determinants of long-term interest rates in the Scandinavian countries - Suzan Hol (Statistics Norway, Research Department, 2006)
The financial markets in a small open economy like the Scandinavian countries are influenced by international economic developments, especially in their major trading partners. This paper investigates to which degree nominal long-term interest rates in Norway, Sweden and Denmark are determined by fundamental domestic macroeconomic variables and by international economic conditions. Relating the level of interest rates to international macroeconomic variables also sheds some light on the degree of financial marketintegration. In Norway the currency risk, exchange rate regime, international debt and unemployment in Europe are significant in explaining the interest rate differential. In Sweden domestic and US inflation are important, while for Denmark domestic debt, domestic and US money stock, and less significantly US inflation are determinants of the interest rate differential. In these three countries with quite different economies the expectations hypothesis, the effect of domestic growth and unemployment and of international growth are not supported as determinants of long-term interest rate differentials.
Keywords: E43; E44; 330; long-term interst rates; expectation hypothesis; international macroeconomic influence; crowding out